Diversidade linguística, cultural e políticas linguísticas: estudo de uma comunidade ucraniana de Irati/PR. - Jacumasso, Tadinei Daniel (2009)
This study aims to study linguistic and cultural diversity and politics linguistics of a Ukrainian community, located at Irati/PR city. Therefore, we make a socio-historical survey about that community, and investigate which languages and in what situations they are used by residents of Itapará community. Furthermore, we refer to the attitudes of speakers with regard to Portuguese and Ukrainian languages. We searched, also, factors that took/take to the preservation of the Ukrainian language, especially related to the church. We base our research on the concepts of sociolinguistics, with focus on the phenomenon of language contact, linguistic attitudes and politics linguistics. Near of the bibliography research we collected narrations from ten speakers from the cited community and we analyzed these reports with the proposed topics of cultural and linguistic diversity and politics linguistics. Among other results, we understand that the conservation and practice of Ukrainian language and culture are strongly linked the religious aspects. Even though the practice of Ukrainian language and culture is on a regression time in the community, we noted that these are part of the identity of speakers.